The impact of banking integration on the profitability of Islamic banks - Case study of Al Salam Bank of Bahrain and Emirates Islamic Bank - - Doufi, Garmia (Milev Journal of Research and Studies, 2022)
The global banking arena witnessed many mergers, such as Islamic banks, which witnessed few of them. One of the most important objectives of the merger is maximizing profits, especially if Islamic banks are considered as profit-oriented banking institutions in addition to their economic, social and developmental functions. A statistical indication of the integration of the profitability of Al Salam Bank of Bahrain and Emirates Islamic Bank.